2012
DOI: 10.1108/03090561211214609
|View full text |Cite
|
Sign up to set email alerts
|

Modeling quality commitment in service organizations: an empirical study

Abstract: Purpose -The purpose of this paper is to attempt to model the antecedents and consequences of quality commitment among employees in a service organization. Design/methodology/approach -The conceptual model based on extant literature on quality commitment is validated through a study among employees in a consultancy organization in Turkey involved in servicing SMEs. Findings -The conceptual model finds reasonable support through the study. All the proposed antecedents and consequences are found to be linked pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 86 publications
3
8
0
Order By: Relevance
“…The results of this study showed that shared values (hypothesis 1) and commitment (hypothesis 3) positively influenced information sharing between wholesalers, distributors, retailers, and their key trading partners. The results of this study are consistent with the findings of Demirbag, Sahadev, Kaynak, and Akgul [27] and Morgan and Hunt [14]. Demirbag et al [27] revealed that leadership commitment had significant influence on information sharing for both the managerial and nonmanagerial staffs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of this study showed that shared values (hypothesis 1) and commitment (hypothesis 3) positively influenced information sharing between wholesalers, distributors, retailers, and their key trading partners. The results of this study are consistent with the findings of Demirbag, Sahadev, Kaynak, and Akgul [27] and Morgan and Hunt [14]. Demirbag et al [27] revealed that leadership commitment had significant influence on information sharing for both the managerial and nonmanagerial staffs.…”
Section: Discussionsupporting
confidence: 94%
“…The results of this study are consistent with the findings of Demirbag, Sahadev, Kaynak, and Akgul [27] and Morgan and Hunt [14]. Demirbag et al [27] revealed that leadership commitment had significant influence on information sharing for both the managerial and nonmanagerial staffs. Information sharing is important in the integration of supply chain management business process [28].…”
Section: Discussionsupporting
confidence: 94%
“…The concept of commitment is not only developed in the area of the organization, it also develops in the area of quality known as quality commitment. In understanding the concept of quality commitment, Jacson argued tha,t the concept of quality commitment (Quality Commitment) was drawn from the concept of organizational commitment (Organizational Commitment) and the principles of work design [34]. Correspondingly, the quality commitment according to Hashim and Mahmood is the dedication of workers to provide quality service (quality service) and the desire to do more than what is expected [35].…”
Section: 13mentioning
confidence: 99%
“…Correspondingly, the quality commitment according to Hashim and Mahmood is the dedication of workers to provide quality service (quality service) and the desire to do more than what is expected [35]. Quality to commitment is a greater awareness and trust in the importance of greater quality and identification, greater involvement and loyalty to all practices aimed at achieving quality [34]. Debbie Garvey and Andrea Lancaster (2010) stated that, a leader to act as a winner, one of which must have a commitment to quality [21].…”
Section: 13mentioning
confidence: 99%
“…Research has shown that it is difficult to capture team-specific activities through commonly used surveys such as National Aeronautics and Space Administration Task Load Index [29]. This survey (6-point Likert scale) has been used for understanding team dynamics in other successful fields when evaluating group decision support tools [79][80][81][82][83][84][85]. Data analysis will include factor analysis, scale reliability analysis, aggregation analysis, and path analysis [77].…”
Section: Step 2: Test Prototype Effectiveness (36 Min)mentioning
confidence: 99%